2017
DOI: 10.18869/mjiri.31.29
|View full text |Cite
|
Sign up to set email alerts
|

Current status of health index in Tehran: A multidimensional approach

Abstract: Background: Health is an essential component of human rights and the rights are interdependent, indivisible, and correlated. The present study aimed at codifying a multidimensional health index according to multistage index development and describing the status of this index in 22 municipal districts of Tehran. Methods: This study was conducted using the data collected in the second round of Urban HEART Project of Tehran (2012-2013). The sample size was 34 700. To develop a multidimensional health index (MDHI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…In this study, the presence of a person with a disability in the family as a need factors, increased the use of outpatient health service utilization. In line with the results of the present study, the results of various studies, including Fistom Girma et al, ( 1 ) Rezapour et al, ( 54 ), and Kim and Lee ( 23 ), showed that having a disability or a movement restrictions increased the likelihood of HSU ( 1 , 44 , 55 , 56 , 57 ). This issue may be due to these individuals’ need to receive prolonged care and their various health needs.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In this study, the presence of a person with a disability in the family as a need factors, increased the use of outpatient health service utilization. In line with the results of the present study, the results of various studies, including Fistom Girma et al, ( 1 ) Rezapour et al, ( 54 ), and Kim and Lee ( 23 ), showed that having a disability or a movement restrictions increased the likelihood of HSU ( 1 , 44 , 55 , 56 , 57 ). This issue may be due to these individuals’ need to receive prolonged care and their various health needs.…”
Section: Discussionsupporting
confidence: 91%
“…Health is an important factor for the development of societies, and investment in this section can have an indisputable effect on the welfare of the people and the economic growth of the country ( 1 , 2 ). One of the indispensable indicators in evaluating the efficacy of the health care system, especially in low- and middle-income countries, is the prevalence of health service utilization (HSU) ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Spiritual Well-Being (SWB) is one of the psychological factors that can play an important role in reducing the care burden of caregivers. According the World Health Organization, health is a concept with physical, social, psychological and spiritual dimensions [10]. Among these dimensions, SWB is a concept that is less understood and is more challenging.…”
Section: Introductionmentioning
confidence: 99%